The role of IL-33 in depression: a systematic review and meta-analysis - Liu, Renli; Liu, Liping; Ren, Shiying; Wei, Chaojie; Wang, Ying; Li, Dong; Zhang, Wenxin (Frontiers in Psychiatry, 2023)
Depression has long been considered a disease involving immune hyperactivation. The impact of pro-inflammatory cytokines such as TNF-α, IL-1β, IL-6, and IL-8 on depression has been widely studied. However, the effect of IL-33, another pro-inflammatory cytokine, has been less researched. Currently, research on the correlation between IL-33 and depression risk is inconsistent. In response to these divergent results, we conducted a review and meta-analysis aimed at resolving published research on the correlation between IL-33 and depression risk, and understanding the potential role of IL-33 in the development and treatment of depression. After searching different databases, we analyzed 8 studies. Our meta-analysis showed that IL-33 had a positive correlation with reduced risk of depression. The pooled standard mean differences (SMD) = 0.14, 95% confidence interval (CI): 0.05–0.24. Subgroup analysis results showed that IL-33 and ST2 levels in cerebrospinal fluid and serum is positive correlated with reduced risk of major depressive disorder (MDD) and bipolar disorder (BD). According to the characteristics of the included literature, the results mainly focuses on Caucasian. Furthermore, according to the subgroup analysis of depression-related data sources for disease or treatment, the correlation between IL-33 and depression risk is reflected throughout the entire process of depression development and treatment. Therefore, the change of IL-33 level in serum and cerebrospinal fluid can serve as useful indicators for assessing the risk of depression, and the biomarker provides potential treatment strategies for reducing the burden of the disease.